2017
DOI: 10.1002/jcsm.12236
|View full text |Cite
|
Sign up to set email alerts
|

miR‐422a suppresses SMAD4 protein expression and promotes resistance to muscle loss

Abstract: BackgroundLoss of muscle mass and strength are important sequelae of chronic disease, but the response of individuals is remarkably variable, suggesting important genetic and epigenetic modulators of muscle homeostasis. Such factors are likely to modify the activity of pathways that regulate wasting, but to date, few such factors have been identified.MethodsThe effect of miR‐422a on SMAD4 expression and transforming growth factor (TGF)‐β signalling were determined by western blotting and luciferase assay. miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…miR‐422a is only present in primates and is expressed from an intragenic region. Circulating levels of miR‐422a were originally inversely associated with muscle strength and size in patients with COPD (Paul et al ., ). In the muscle, expression of miR‐422a was higher in patients than in controls but surprisingly miR‐422a expression was directly proportional to muscle size in COPD patients but not in normal healthy elderly individuals.…”
Section: Fine‐tuning the Muscle Proteome By Micrornas: Do Mirnas Contmentioning
confidence: 97%
See 3 more Smart Citations
“…miR‐422a is only present in primates and is expressed from an intragenic region. Circulating levels of miR‐422a were originally inversely associated with muscle strength and size in patients with COPD (Paul et al ., ). In the muscle, expression of miR‐422a was higher in patients than in controls but surprisingly miR‐422a expression was directly proportional to muscle size in COPD patients but not in normal healthy elderly individuals.…”
Section: Fine‐tuning the Muscle Proteome By Micrornas: Do Mirnas Contmentioning
confidence: 97%
“…Consistent with this suggestion, SMAD4 was identified as a target of miR‐422a and transfection of human skeletal myoblasts with miR‐422a inhibited TGF‐β signalling. As canonical TGF‐β signalling is dependent on SMAD4, these data suggest that at least one mechanism by which miR‐422 provides resistance to muscle wasting is through the inhibition of SMAD‐dependent wasting (Paul et al ., ). These data suggest a microRNA‐dependent mechanism that regulates the TGF‐β signalling pathway in skeletal muscle as shown in Fig.…”
Section: Fine‐tuning the Muscle Proteome By Micrornas: Do Mirnas Contmentioning
confidence: 97%
See 2 more Smart Citations
“…Elevated miR-424-5p expression in patients with muscle wasting might contribute to the inhibition of protein synthesis and loss of muscle mass (88). It was demonstrated that miR-422a, as a suppressor of TGF-β signaling by reducing the expression of SMAD4 protein, might attribute to the maintenance of muscle mass (89).…”
Section: Inflammatory Diseasesmentioning
confidence: 99%